Predisposing and enabling factors influencing the utilisation of maternal healthcare services at fishing landing sites in Buikwe district, Uganda - Namukasa, Rashidah; Ekakoro, Newton; Amatre, Gerald; Kaddumukasa, Martha (International Journal Of Community Medicine And Public Health, 2024)
Background: Studies have demonstrated that women who get professional healthcare personnel’s prenatal, delivery, and postnatal care have better pregnancy outcomes, which lowers the incidence of both neonatal and mother deaths. Uganda is among the sub-Saharan African countries with the highest percentages of maternal deaths of which the majority of the deaths take place in remote, resource-constrained areas, such as fishing landing sites. We investigated the factors influencing the use of maternity healthcare services by women from remote Lake Victoria islands fishing settlements in the Buikwe district of Uganda. Methods: A cross-sectional study design with a quantitative approach was used. One hundred and four mothers were recruited in the study carried out at Ssenyi, Kiyindi and Nkombwe landing site in Buikwe district. Questionnaires were used to obtain information from mothers about predisposing factors, and enabling factors. Multinomial logistic regression was used to determine which factors influenced the use of maternal healthcare services. Results: Marital status (p=0.045, aOR=0.582; 95% CI=0.163-2.082) and paternal occupation (p=0.017, aOR=1.335; 95% CI=0.059-8.348) were the factors influencing maternal healthcare service utilisation among the respondents. Conclusions: Increasing the amount of actions meant to raise socioeconomic standing and involving the men in maternal health seeking might aid in enhancing maternal healthcare services use by women at the landing sites in Uganda.